An audit of pharyngeal gonorrhoea treatment in a public sexual health clinic in Adelaide, South Australia. (May 2013) - Hustig, A; Bell, C; Waddell, R
Summary: In recent times there have been changes to guidelines regarding the management of gonorrhoea, from both the Centers for Disease Control and Prevention in 2010 and the British Association for Sexual Health and HIV (BASHH) in 2011. Coinciding with their release we conducted a clinical audit of our treatment protocol for gonorrhoea. In 2010, local data on the minimum inhibitory concentrations for Neisseria gonorrhoeae indicated an increase in local isolates that were less sensitive to ceftriaxone (11.6% c.f. 5.3% in 2009). We have a long history of using 250 mg of ceftriaxone to treat all standard sites of gonorrhoea infection followed with tests of cure in all cases. In a retrospective clinical audit of an 11-year period from 2000 up to and including 2010 we identified six test-of-cure failures over 11 years after treating a total of 215 patients with pharyngeal gonorrhoea.